0885 Reduction in Emergency Department and Inpatient Hospitalization Visits and Length of Stay in a Cohort of Pediatric Patients Initiated on Positive Airway Pressure for Obstructive Sleep Apnea Syndrome. (27th May 2020) - Xanthopoulos, M S; Williamson, A A; Tapia, I E; Cielo, C M; Ku, H; Smith, J; Matthews, E; Beck, S E
Abstract: Introduction: Positive Airway Pressure (PAP) is an efficacious treatment of pediatric obstructive sleep apnea syndrome (OSAS). However, it is unknown whether PAP initiation is associated with reduced healthcare utilization, an important metric of care management. We hypothesized that healthcare utilization would be reduced after initiation of PAP in a cohort of pediatric patients prescribed PAP for OSAS. Methods: Data were extracted from electronic medical records of 475 patients (Mean±SD age at PAP initiation=7.7±5.7 years; 58.7% male; 40.6% White; 38.3% Black; 18.1% multiracial/other; 12.1% Hispanic/Latinx) prescribed PAP for OSAS and followed in our Sleep Center quality improvement program. We extracted the total number of emergency department (ED) visits and hospitalizations and computed the related average length of stay (LOS) in hours for these visits in the 18 months prior to and 18 months following PAP initiation. Results: Paired samples t-tests showed that number of ED visits and hospitalizations, and the related visit LOS, were significantly reduced following PAP initiation. The average number of visits reduced from 2.20 pre-PAP to 1.77 post-PAP initiation [t(474) = 3.48, p<.001, effect size = 0.16], while average LOS reduced from 185.14 hours pre-PAP to 42.94 hours post-PAP initiation [t(474) = 4.81, p<.001, effect size = 0.29]. Findings for the significant reduction in LOS held after adjusting for the number of pre and post-PAP ED visits and hospitalizations, average pre-PAP LOS, and patient demographics (age at the time of initiation; sex; race/ethnicity) using multiple linear regression. Conclusion: PAP initiation was associated with fewer and shorter ED visits and hospitalizations in a large sample of pediatric patients. We speculate that PAP initiation could help reduce morbidity associated with pediatric OSAS, as well as improve healthcare utilization, capacity management and care in this population. Support: K23HD094905 and Sleep Research Foundation (AAW)